Hypopharyngeal Perforation Mimicking Esophageal Atresia: A Case Report of an Extremely Low Birth Weight Infant Emphasizing the Need for Preoperative Endoscopy. Issue 3 (March 2021) - Kaufmann, Jost; Laschat, Michael; Schieren, Mark; Böckenholt, Kai; Klein, Tobias; Wappler, Frank
Abstract : We report a case of an extremely low birth weight premature infant born at 27 weeks of gestation, transferred to our tertiary pediatric referral center for surgical repair of an esophageal atresia. Endoscopic evaluation before the start of surgery revealed a hypopharyngeal perforation, resulting in the false impression of esophageal atresia. If no tracheoesophageal fistula is found during tracheoscopy, esophagoscopy should be done before surgical intervention as the inability to pass a nasogastric tube into the stomach is not sufficiently reliable for a correct diagnosis of esophageal atresia. Abstract : Supplemental Digital Content is available in the text.